Mini Review of Revenue: Profit and Growth - Endah Suci Damayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research Objectives to provide an overview of existing results from previous research and provide conclusions by researchers. The research method used is a literature review derived from existing scientific articles from various journals in the world related to variables.The results of research in this study provide significant results with quantitative research methods and mostly use qualitative methods with the results of the researcher's perspective. The researcher highlighted that in finance there are other variables that can be used in the future by researcher.